Effect of earthquake energy input characteristics on hysteretic damper efficiency. - Yamaguchi, Hiroki (Earthquake engineering & structural dynamics.)
Robust performance of hysteretic dampers, used in controlling mid rise buildings, against change of earthquake characteristics is investigated in this paper. A shear type ten storey building incorporating hysteretic dampers is studied as a model under the assumption of elastic perfectly plastic behaviour for inelastic frame and damper deformations. An energy based damper performance index is used to evaluate damper overall efficiency. Thirty five earthquake records are applied and the damper strength is optimized for each earthquake record to obtain the maximum performance index or the damper efficiency. Based on the obtained numerical results it is found that, besides the effect of maximum energy input on damper efficiency, other time dependant properties such as energy based effective duration and earthquake dominant period have great influence on the damper efficiency. A factor (x), which represents the combined effect of maximum energy input, effective duration and dominant earthquake period, is also derived for the prediction of damper efficiency.